The Precarious State of Letter C: Land Registration Law Dynamics After PP Number 18 Year 2021 - Naning indriyawati; Suyanto Suyanto; Dara Puspitasari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The enactment of Government Regulation (PP) No. 18 of 2021 has triggered a major transformation in Indonesia’s land registration framework. The primary focus of this study is to evaluate the current legal status of